Phenotypic Performance and Early Selection of Three Cayenne Pepper (Capsicum frutescens L.) Varieties in Response to Gamma Irradiation - Firnanda Ranggawikya; Theresa Dwi Kurnia; Yuniel Melvanolo Zendrato (Jurusan Agroteknologi, 2026)
The development of cayenne pepper (Capsicum frutescens L.) varieties through mutation breeding represents a strategic approach to enhancing agricultural productivity and food security. This research aimed to evaluate phenotypic diversity and select mutant genotypes from three distinct cayenne pepper varieties induced by gamma radiation. The study was conducted using a two-factor experiment: three cayenne pepper varieties and five gamma ray dose ranges (0, 100, 200, 300, and 400 Gy), arranged in a randomized complete block design (RCBD) with three replications. The results demonstrated that the interaction between varieties and irradiation doses significantly influenced seed viability, growth characteristics, and yield components. High irradiation doses (300 and 400 Gy) caused a drastic reduction in germination rates, falling as low as 42.50%, and increased seedling mortality up to 87.50%. Conversely, low-to-moderate doses effectively expanded quantitative variability in plant height, flowering age, and fruit dimensions. Quantitative analysis revealed that selected mutant genotypes exhibited superior phenotypic performance; genotype V2G1 demonstrated the highest yield potential with an average fruit weight of 3.26 g, while genotype V3G1 exhibited a desirable early-maturing trait. While qualitative characters such as fruit shape and plant growth habit remained largely stable, significant quantitative shifts confirmed the effectiveness of gamma radiation to increase the phenotypic variability. Based on a selection index integrating multiple agronomic traits, three mutant genotypes (V2G1, V3G1, and V1G1) were identified as the candidates for further improvement in chili breeding programs. Key words: Cayenne pepper, gamma irradiation, mutation breeding, phenotypic, selection index. ABSTRAK Pengembangan varietas unggul cabai rawit (Capsicum frutescens L.) melalui pemuliaan mutasi merupakan pendekatan strategis untuk meningkatkan produktivitas pertanian dan ketahanan pangan. Penelitian ini bertujuan untuk mengevaluasi keragaman fenotipik serta menyeleksi genotipe mutan unggul dari tiga varietas cabai rawit yang diinduksi dengan radiasi gamma. Penelitian dilakukan menggunakan percobaan dua faktor: tiga varietas cabai rawit dan lima dosis sinar gamma (0, 100, 200, 300, dan 400 Gy ) yang disusun dalam rancangan kelompok lengkap teracak (RKLT) dengan tiga ulangan. Hasil penelitian menunjukkan bahwa interaksi antara varietas dan dosis iradiasi berpengaruh nyata terhadap viabilitas benih, karakter pertumbuhan, dan komponen hasil. Dosis iradiasi tinggi (300 dan 400 Gy) menyebabkan penurunan drastis pada tingkat perkecambahan hingga mencapai 42,50% serta meningkatkan mortalitas bibit hingga 87,50%. Sebaliknya, dosis rendah hingga sedang efektif dalam meningkatkan keragaman kuantitatif pada tinggi tanaman, umur berbunga, dan dimensi buah. Analisis kuantitatif menunjukkan bahwa genotipe V2G1 menunjukkan potensi hasil tertinggi dengan rata-rata bobot buah 3,26 g, sedangkan genotipe V3G1 memiliki sifat genjah yang diinginkan dengan waktu berbunga. Sementara itu, karakter kualitatif seperti bentuk buah dan tipe pertumbuhan tanaman relatif stabil, perubahan kuantitatif yang signifikan mengonfirmasi efektivitas radiasi gamma dalam meningkatkan variabilitas fenotipik. Berdasarkan indeks seleksi yang mengintegrasikan berbagai sifat agronomis, tiga genotipe mutan (V2G1, V3G1, dan V1G1) diidentifikasi sebagai kandidat untuk pengembangan program pemuliaan cabai ke depan. Kata kunci: cabai rawit, fenotipik, iradiasi gamma, pemuliaan mutasi, indeks seleksi.